2010
DOI: 10.1007/s11224-010-9612-z
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase conformations and exciton couplings in 5,6,11,12-tetrahydrodibenzo[a,e]cyclooctene

Abstract: The conformations and exciton couplings in 5,6,11,12-tetrahydrodibenzo[a,e]cyclooctene (THDC) have been studied using resonance-enhanced two-photon ionization spectroscopy in a supersonic jet expansion. It has been estimated from the spectral analysis that 90% of THDC exists in the twist-boat (TB) conformation; the chair (C) conformer constitutes the remaining 10%. Most of the vibronic activity in the spectrum of THDC is associated with the symmetric flapping of the aromatic rings of the TB conformer. The obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Specifically, TM-DBCOD was synthesized from (4,5-dimethyl-1,2-phenylene)dimethanol (di-OH) on a large scale, sequentially through bromination 49 using phosphorous tribromide and dimerization [50][51] in the presence of lithium sands. 1,10-di-CHO was formed via Rieche formylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, TM-DBCOD was synthesized from (4,5-dimethyl-1,2-phenylene)dimethanol (di-OH) on a large scale, sequentially through bromination 49 using phosphorous tribromide and dimerization [50][51] in the presence of lithium sands. 1,10-di-CHO was formed via Rieche formylation.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, TM-DBCOD was synthesized from (4,5-dimethyl-1,2-phenylene)­dimethanol (di-OH) on a large scale, sequentially through bromination using phosphorus tribromide and dimerization , in the presence of lithium sands. 1,10-di-CHO was formed via Rieche formylation. , One-step column purification of 1,10-di-CHO was adequate instead of the multistep column purification required for the preparation of 2,9-di-CHO (Scheme S1 and Figures S1 and S2).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Hamza [201] report on the synthesis of 5,6,11,12-tetrahydrodibenzo[a,e]cyclooctene (THDC) and its two selectively deuterated isotopomers which were studied by resonance-enhanced two-photon ionization spectroscopy in a supersonic jet expansion. The results showed that about 90% of THDC in the gas phase exists in the twist-boat and the remaining 10% in chair conformation.…”
Section: Issuementioning
confidence: 99%
“…Good agreement between experimental results and theoretical results was reached. We look forward to studies comparing the findings of Hamza [201] to this article.…”
Section: Issuementioning
confidence: 99%
“…The thermal isomerization of DBCO between the twist-boat and chair isomers has been thoroughly investigated using DFT calculations, , X-ray crystallography, variable temperature NMR spectroscopy, and differential scanning calorimetry (DSC) . However, to the best of our knowledge, previous studies have yet to consider the influence of regiochemistry on the isomerization equilibrium.…”
mentioning
confidence: 99%